The Development of Learning Services Assessment Instrument Model of Islamic Higher Education - Zurqoni, Zurqoni (Dinamika Ilmu, 2017)
The Islamic higher educations have an important role in producing the qualified graduates. Therefore, the organization of the Islamic higher educations must be coupled with the quality of learning services. Some institutes and universities are optimizing their learning services, while the others tend to choose different service patterns since there is no standard instrument of the quality of the learning service. This research was conducted to develop an assessment instrument model to measure the learning services in Islamic higher education. This research applied a research and development approach through three stages, namely: pre-development, development, and application of the model. The development of the instrument was done through individual, small group, and large group testing through field tests involving students of Islamic higher education. The instrument model includes the aspects of tangibles, reliability, responsiveness, empathy, and assurance along with the indicators, which is, analyzed using Confirmatory Factor Analysis. The findings of the research shows that learning assessment instrument model of Islamic higher education developed by integrating some aspects categorized as goodness of fit, which is, proved by Lambda score (λ)> 0,30, ρ-score (p)> 0, 05, Root Mean Square Error of Approximation (RMSEA) <0.08, and Goodness of Fit Index (GFI> 0.90). The developed instrument has high validity, while the aspects of learning services meet the requirements and are reliably to assess learning services at Islamic Higher Education